Sistem Informasi Pengelolaan Buku Kas Mahasiswa Berbasis Web - Asri Bella Sari; Munawir; Teuku Armel Fahlevi; Siti Nurchaliza; Arman Yuliando; Tawang Fadhila; Rahmina Sari Tinendung; Aulia Zahra (JURUTERA - Jurnal Umum Teknik Terapan, 2020)
With the internet connection, information can be accessed quickly by anyone and anywhere. As well as with automatic and integrated data processing, calculations and data storage can be carried out quickly, and the results will be known directly with accurate data. Currently, the management and recording related to cash in and cash out on campus are carried out very simply and not in accordance with existing accounting records and do not take into account the evidence that supports accounting records. In this university, there is also no financial report in any form. A system is needed that can store all transactions related to cash in and cash out to control all existing transactions and calculate cash data reports so that the owner can find out the ending balance each month. The plan of making a web application to manage cash receipt and disbursements transactions. Making this web-based application, use PHP with MySQL database. With this application, the university can find out every transaction that exists, and the owner can view cash data reports.